Paclitaxel and Mortality Following Peripheral Angioplasty: An Adjusted and Case Matched Multicentre Analysis. (August 2020) - Saratzis, Athanasios; Lea, Talia; Yap, Trixie; Batchelder, Andrew; Thomson, Benedict; Saha, Prakash; Diamantopoulos, Athanasios; Saratzis, Nikos; Davies, Robert; Zayed, Hany
Abstract : Objective: Paclitaxel based drug coated balloons (DCBs) and drug eluting stents (DESs) may be associated with increased mortality in patients with peripheral arterial occlusive disease (PAOD), based on a recent meta-analysis. This study, however, had a number of limitations, which have been discussed at great length among the vascular community. The aim of this research was to assess the association between paclitaxel based endovascular treatment (PTX) in the femoropopliteal (F–P) segment and mortality, adjusting for relevant risk factors and including patients with chronic limb threatening ischaemia (CLTI). Methods: This was a retrospective cohort study of a prospectively maintained multicentre (three sites) database of patients with claudication or CLTI. Patients having F–P angioplasty between 1 January 2014 and 30 May 2019 with or without PTX were included. Survival was compared in Cox regression analyses adjusted for parameters of the Charlson comorbidity index. A separate nested case matched (based on each individual's Charlson index) analysis was performed to compare mortality rates between those who received PTX and those who did not. Results: A total of 2 071 patients were analysed: 966 patients (46.6%) were treated with PTX (952 [46%] had CLTI and 1 119 [54%] severe claudication [Rutherford stage 3]). Over a 24 month median follow up, 456 (22.1%) patients died. Using multivariable Cox regression, PTX was not associated with mortality (HR 0.94, p  = .46), even when assessed separately for those with intermittent claudication (HR 1.30, p  = .15) or CLTI (HR 0.81, p  = .060). In the case matched analysis (885 matched pairs of patients), PTX was not associated with mortality (HR 0.89, p  = .17). Paclitaxel dose and use of a DCB or DES were not associated with mortality in any subanalysis. Conclusion: When relevant risk factors were taken into account, there were no associations between PTX and mid term mortality in patients with PAOD.